Komunikasi Partisipatif Kepala Sekolah dalam Mengembangkan Kolaborasi dengan Komunitas dan Stakeholder - Zahria, Ismi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study aims to explore the communication strategies employed by the school principal in building collaboration with the community and stakeholders at SMK Diponegoro Tumpang. The principal plays a key role in improving the quality of education through participatory communication, involving parents, teachers, and the local community in decision-making. This research employs a qualitative method with a case study approach, conducting in-depth interviews with the principal to understand the challenges and successes in building collaboration. The findings indicate that the principal's use of face-to-face and digital communication successfully increased stakeholder engagement and strengthened support for school programs. However, the main challenges identified include the digital divide and differing expectations among stakeholders. This study highlights the importance of open, participatory, and flexible communication to ensure successful collaboration between schools and the community.